Relationships between sequestration, antigenic variation and chronic parasitism in Plasmodium chabaudi chabaudi--a rodent malaria model. - Gilks, C; Walliker, D; Newbold, C (1990)
We describe here a rodent malaria model using cloned lines of Plasmodium chabaudi chabaudi in inbred CBA/Ca mice that exhibits both clonal antigenic variation in late stage-specific surface antigens, and deep vascular schizogony in the liver. We show that both these features are modulated by the spleen, and that surface antigen expression is crucially involved in the sequestering phenotype. Surface antigens are variant in chronic infection, and host protective immune responses can distinguish between these variants. Splenectomy abolishes this difference. The acute infection with non-sequestering cloned lines is kinetically indistinguishable from sequestering clones, but parasites unable to express variant sequestration-associated antigen do not form a chronic recrudescing infection. Another clone, able to re-express this antigen in the presence of the spleen, undergoes typical chronic recrudescence. In this model, the biological significance of sequestration-associated variant antigen seems to enable the establishment of chronic infection in the presence of a primed spleen.